Whole exome sequencing identifies variants in the \(TNNI3\) gene in vietnamese patient with restrictive cardiomyopathy - a case report - Lien, Nguyen Thi Kim; Nguyen, Van Tung; Le, Trong Tu; Dang, Thi Hai Van; Vu, Quynh Nga; Nguyen, Thanh Hien; Do, Minh Hien; Nguyen, Hoang Lam; Trinh, Tuan Hien; Nguyen, Minh Duc; Nguyen, Huy Hoang (Academia Journal of Biology, 2024)
Restrictive cardiomyopathy (RCM) is a rare heart muscle disease in which the heart wall is rigid leading to diastolic dysfunction caused by abnormal elastic properties of the myocardium and/or intercellular matrix. The prognosis is generally poor, and RCM has a high mortality rate in pediatric patients. There are no curative treatments for RCM, so cardiac transplantation is the only effective treatment. Diagnosis RCM, clinical diagnosis can be challenging because clinical presentations and imaging manifestations of RCM are similar to other cardiomyopathies so it requires other specific diagnoses. Currently, pathogenic mutations in 22 different genes have been identified in patients with RCM. Identifying mutations in these genes helps discriminate RCM from other cardiomyopathies. Besides, next-generation sequencing (including whole genome sequencing, whole exome sequencing,...) has provided an effective tool for simultaneously analyzing mutations in many different genes.In this study, we conducted sequencing of the entire gene coding region (WES) in the patient and identified a compound heterozygote variants (c.289C>G, p.Arg97Gly and c.433C>T, p.Arg145Trp) in the TNNI3 gene. These variants were inherited from the patient's father and mother, who were heterozygous variant carriers. These variants were also identified as the pathogenic variants in the ClinVar database (accession number VCV001331910.2 and VCV000012426.28, respectively) and were the cause of the patient's disease. Our results suggest that WES can be used to definitively diagnose the genetic variants associated with RCM and show that genetic screening is essential for families of RCM patients.